2013
DOI: 10.1371/journal.pone.0076810
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Interleukin-6 –174 G>C Gene Promoter Polymorphism on Neuroblastoma

Abstract: BackgroundCommon variants in DNA may predispose to onset and progression of neuroblastoma (NB). The genotype GG of single nucleotide polymorphism (SNP) rs1800795 (−174 G>C) in interleukin (IL)-6 promoter has been associated with lower survival of high-risk NB.ResultTo evaluate the impact of IL-6 SNP rs1800795 on disease risk and phenotype, we analyzed 326 Italian NB patients and 511 controls. Moreover, we performed in silico and quantitative Real Time (qRT)-PCR analyses to evaluate the influence of the SNP on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Two phenotypes for this polymorphism have been identified: the 174 G/G and 174 G/C genotypes as the high-producer phenotype; and the 174 C/C genotype as the low-producer phenotype 10 12. The 174 G/C phenotype has been reported to be associated with the diseases with inflammatory background such as juvenile chronic arthritis,10 Alzheimer disease,13 type 2 diabetes,14 atherosclerosis,15 osteoporosis,16 cardiovascular diseases,17 18 and also multiple cancers including hepatocellular,19 colorectal,20 prostate,21 ovarian22 and breast cancer23 as well as Hodgkin's lymphoma24 and neuroblastoma 25…”
Section: Structure and Regulation Of Interleukinmentioning
confidence: 99%
“…Two phenotypes for this polymorphism have been identified: the 174 G/G and 174 G/C genotypes as the high-producer phenotype; and the 174 C/C genotype as the low-producer phenotype 10 12. The 174 G/C phenotype has been reported to be associated with the diseases with inflammatory background such as juvenile chronic arthritis,10 Alzheimer disease,13 type 2 diabetes,14 atherosclerosis,15 osteoporosis,16 cardiovascular diseases,17 18 and also multiple cancers including hepatocellular,19 colorectal,20 prostate,21 ovarian22 and breast cancer23 as well as Hodgkin's lymphoma24 and neuroblastoma 25…”
Section: Structure and Regulation Of Interleukinmentioning
confidence: 99%
“…And IL-6 -174 CC genotype was associated with increased renal cancer risk [13] and bladder cancer risk [14]. While a case-control study from Italy reported that IL-6-174G > C polymorphism might be related to onset and progression of neuroblastoma [15] and it might be a carcinogenetic factor in the diffuse type gastric adenocarcinoma [16]. Meanwhile, as for IL-6-572C > G polymorphism, it was reported to influenced susceptibility of HBV-related hepatocellular carcinoma according to Tang S's case research [17].…”
Section: Discussionmentioning
confidence: 96%
“…Among these, the most studied SNP at position -174 (IL-6 -174G/C) can modify transcriptional regulation and cytokine levels, and has an impact on inflammatory phenotypes (Fishman et al, 1998). Previous studies have shown that IL-6 -174 G/C polymorphism is associated with the development and progression of various human diseases including systemic lupus erythematosus, neuroblastoma, coronary heart disease, HIV/AIDS, and nephritis (Sobti et al, 2010;Santos et al, 2011;Yin et al, 2012;Totaro et al, 2013;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%